Thirteen national brazilian nursing research congress (SENPE) june 2005, São Luiz, Maranhão - Cruz, Isabel Cristina Fonseca da (Online Brazilian Journal of Nursing, 2004)
Make plans now to attend the Thirteen National Brazilian Nursing Research Congress in June 14-17th, 2005. This meeting will be held in São Luis, Maranhão, Brazil.The objectives are: promote the exchange of research and clinical scholarship in an national/international forum; advance the science of nursing by disseminating research findings that influence practice, education, administration and health care policy; and explore opportunities for national/international collaboration in nursing research, practice, education, administration and health care policy.HOTEL AND TRAVEL Learn more about the ammenities and setting of São Luis, Maranhão, Brazil, athttp://www.cidadeshistoricas.art.br/saoluis/ or http://www.wojner.de/slz/ (in English).Informations at : http://www.visaoperfileventos.com.br/eventos.htm aben@abennacional.org.br or http://www.abennacional.org.br/